Broad ligament hernia successfully treated by laparoscopy: Case report and review of literature. Issue 4 (November 2014) - Matsunami, Masatoshi; Kusanagi, Hiroshi; Hayashi, Ken; Yamada, Shigetoshi; Kano, Nobuyasu
Abstract We report a case of a 36‐year‐old woman with a history of caesarean section who presented with small bowel obstruction. Abdominal multi‐detector CT showed discontinuity of the small bowel near the broad ligament on the left. We made a provisional diagnosis of an internal hernia through a defect in the broad ligament and performed laparoscopic exploration, which revealed a viable ileal loop incarcerated by the broad ligament. Multi‐detector CT may be useful for diagnosing this type of defect preoperatively, whereby open surgery can be avoided.